Nursing care for oncological wounds: knowledge of resident nurses (Research, Society and Development, 2022)
Objective: to describe the knowledge of nursing residents about assessment and nursing care for patients with oncological wounds. Method: this is a descriptive, cross-sectional, qualitative approach. The survey was carried out with 67 first and second year nursing residents. To obtain the data, a semi-structured electronic form was sent, composed of questions about social and cognitive aspects, previous experiences and specific knowledge about oncological wound care. difficulty in caring for a person with an oncological wound. Although some of these professionals sought training courses, most of them did not address the issue. Conclusion: the study highlighted the need to fill in the knowledge gaps of residents, who are between the role of students and professionals. Therefore, it is important that undergraduate courses, health institutions, recognize the importance of the theme and that they approach its development with their professionals and students to improve the quality of care for patients with oncological wounds.